Antimicrobial Drug-Resistant Salmonella in Urban Cats: Is There an Actual Risk to Public Health? - János Dégi; Kálmán Imre; Viorel Herman; Iulia Bucur; Isidora Radulov; Oana-Cătălina Petrec; Romeo Teodor Cristina (MDPI AG, 2021)
The present study was undertaken to investigate the presence of Salmonella spp. in the faeces of client-owned cats in urban areas and to evaluate the risk that is posed to public health. Fresh faecal samples were collected directly from the rectums from 53 diarrhoeic and 32 non-diarrhoeic cats. The samples were individually screened for the presence of Salmonella spp. using standard methods and, in the case of positive findings, the resulting typical colonies were then biochemically confirmed using the VITEK®2 automated system. Subsequently, all of the Salmonella spp. isolates were molecularly tested for the presence of the invA gene. All of the isolates were serotyped using the slide agglutination technique according to the White-Kauffmann-Le Minor scheme. The phenotypic antimicrobial susceptibility profile of the isolated strains was obtained from the VITEK®2 system using specific cards from the Gram-negative bacteria. A total of 16 of the samples (18.82%) tested positive for Salmonella spp. according to conventional and molecular testing methods. Serotyping of the Salmonella isolates showed the presence of three serotypes, namely S. enteritidis (n = 9; 56.3%), S. typhimurium (n = 4; 25%), and S. kentucky (n = 3; 18.8%). All of the tested strains showed strong resistance towards cefazolin, cefepime, ceftazidime, and ceftriaxone. Additionally, resistance (listed in descending order of strength) was observed to trimethoprim/sulfamethoxazole (11/16; 68.8%), ampicillin (10/16; 62.5%), ampicillin/sulbactam (9/16; 56.3%), gentamicin (9/16; 56.3%), nitrofurantoin (8/16; 50.0%), and amikacin (5/16; 31.3%). No resistance was expressed against ciprofloxacin, ertapenem, imipenem, levofloxacin, piperacillin/tazobactam, and tobramycin. The results of this study highlight a substantial public health issue and medical concern, especially in vulnerable people, such as children, the elderly, and immunocompromised individuals.